Dopamine facilitates Al2O3 film growth on polyethylene terephthalate by low-temperature plasma-enhanced atomic layer deposition. (26th November 2022) - Zhang, Zhen; Yan, Chi; Liu, Cui; Ye, Xiaojun; Yuan, Xiao; Li, Hongbo
Abstract: Polymeric materials, including polyethylene terephthalate (PET), are widely used in various fields because of their beneficial properties. Functional films are deposited on these materials through different approaches, such as plasma-enhanced atomic layer deposition (PEALD), to enhance their performance and prolong their life span. However, the inert and thermally fragile nature of most polymers hinders deposition. We developed a strategy for the PEALD of nanoscale Al2 O3 films on PET substrates. First, a PET substrate is subjected to alkali treatment, which gives it basic hydrophilicity for the subsequent dopamine modification. After 24 h of dopamine deposition, the substrate shows adequate active sites (phenolic hydroxyl groups), which can chemisorb large amounts of precursor during the initial deposition. The island growth mode was observed during the PEALD processes. We analyzed the detailed chemical components of Al2 O3 on alkali-treated PET and dopamine-modified PET. After 100 cycles of deposition, the Al2 O3 films on both samples contained much hydrogen. Benefitting from the more active sites, we observed more continuous Al2 O3 film on dopamine-modified PET, which exhibited excellent water vapor blocking performance. Our findings suggest that dopamine could act as a 'bridge' between polymers and PEALD functional films.